Artificial maturity : helping kids meet the challenge of becoming authentic adults - Elmore, Tim. (San Francisco : Jossey-Bass, 2012)
"How to raise kids who can handle the real worldToday's Generation iY (teens brought up with the Internet) and Homelanders (children born after 9/11) are overexposed to information at an earlier age than ever and paradoxically are underexposed to meaningful relationships and real-life experiences. Artificial Maturity addresses the problem of what to do when parents and teachers mistake children's superficial knowledge for real maturity. The book is filled with practical steps that adults can take to furnish the experiences kids need to balance their abilities with authentic maturity. Shows how to identify the problem of artificial maturity in Generation iY and Homelanders Reveals what to do to help children balance autonomy, responsibility, and information Includes a down-to-earth model for coaching and guiding youth to true maturity Artificial Maturity gives parents, teachers, and others who work with youth a manual for understanding and practicing the leadership kids so desperately need to mature in a healthy fashion"--
Machine generated contents note: 1. What Is Artificial Maturity? -- 2. We Didn't See It Coming -- 3. Who Is Generation iY? -- 4.A Balancing Act -- 5. The Problem of Atrophy -- 6. The Problem with Talent -- 7. The Pull to Be a Karaoke Parent or Teacher -- 8. Turning Artificial Maturity into Authentic Maturity -- 9. The Future of Parenting and Education -- 10. What Will Kids Look Like in the Future? -- 11. Correcting and Connecting -- 12. Becoming a Soul Provider -- 13. The Big Picture -- 14. Passing the Baton.
Includes bibliographical references and index.
Keywords: Adolescence; Emotional maturity; Adolescent psychology; Young adults -- Psychology; Parenting; FAMILY & RELATIONSHIPS -- Parenting -- General; Adolescence; Adolescent psychology; Emotional maturity; Parenting; Young adults -- Psychology; Jugend; Erwachsenwerden; Zwischenmenschliche Beziehung; Autonomie; Erziehung